Die uitbeelding van swart mense in Suid-Afrikaanse skoolgeskiedenishandboeke - Corene de Wet (Acta Academica, 2001)
Curriculum 2005 and the Chisholm Report tolled the knell of history as an individual discipline in South African schools. In future history will form part of the human and social sciences. The purpose of this article is to provide an overview of the portrayal of black people in school history textbooks. It appears that 1994 was a watershed year. Before then, black people were represented as faceless, peripheral figures in school history textbooks. Their actions, religion and civilisation were strongly criticised. After the first democratic election a total paradigm shift occurred. School history textbooks now represent the view of black people; hence white colonists and the apartheid regime have become the target of scathing criticism.